Predictors of seatbelt and helmet usage among victims seeking care at emergency department in a tertiary care hospital in rural Northern India. - Chaudhary, C; Singh, A; Pathak, R; Ahluwalia, SK; Goel, RKD; Mithra, P (Nepal Journal of Medical Sciences, 2013)
Background: Despite the introduction of seat belt and helmet legislation their use in India is still not satisfactory. The present study was therefore conducted to assess the prevalence of and factors associated with safety belt and helmet non-use among Emergency Department (ED) patients seeking care at a tertiary care teaching hospital. Methods: The present cross sectional study with systematic sampling was carried out among stable, non-urgent ED patients aged more than 18 years using pretested questionnaire during July to December 2011. Safety belt use was defined via two methods: a single-item and a multiple-item measure of safety belt use. Results: Outcome for multivariate logistic regression analysis was safety belt use less than ‘always’. Of 350 patients approached, 280 (80%) participated. The prevalence of safety belt/helmet use ‘always’ was 31% and 16% respectively using two different survey measures. Male gender, maximum alcohol consumption of greater than 5 drinks in a single episode, riding with others that drink and drive, ever receiving a traffic citation for not wearing a safety belt or helmet, the belief that safety belt use is “uncomfortable”, and that “I just forget to use my seatbelt” were risks for safety belt non-use according to the Single Measure of Safety Belt/ Helmet Use, while “it’s my usual habit” was protective. Conclusion: Findings of the study warrants urgent need to take measures or targeted interventions in order to increase safety belt and helmet use among this high risk population. Nepal Journal of Medical Sciences | Volume 02 | Number 01 | Jan-Jun 2013 | Page 57-61 DOI: http://dx.doi.org/10.3126/njms.v2i1.7653